2008
DOI: 10.1213/ane.0b013e31817ef259
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Ultrasound-Guided Infraclavicular Block Using the “Double Bubble” Sign and Neurostimulation-Guided Axillary Block

Abstract: Compared to triple-stimulation axillary block, ultrasound-guided infraclavicular block using the double bubble sign provided a similar efficacy, a shorter performance time and lower procedural pain scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 11 publications
2
48
0
1
Order By: Relevance
“…Our study showed that a 30ml volume of ropivacaine 0.75% is equally efficient as higher volumes in producing an ICB. However, in line with medical literature, our ICB failure rate was not insignificant [1,4,[11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study showed that a 30ml volume of ropivacaine 0.75% is equally efficient as higher volumes in producing an ICB. However, in line with medical literature, our ICB failure rate was not insignificant [1,4,[11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 88%
“…In medical publications the USG-ICB success rate varies from 84% to 96% [1,4,[11][12][13][14][15]. On the basis of the success rate reported in the literature, to calculate the sample size of our study, maintaining a statistical power of at least 90% and a significance level of 5%, the minimal sample size needed to nullify the hypothesis of inferiority of the smaller volume (30 ml vs 35 ml), was 25 patients [16].…”
Section: Methodsmentioning
confidence: 99%
“…Tran et al [42 ] compared infraclavicular blocks guided by ultrasound and axillary blocks guided by nerve stimulation in a randomized study of 70 adult patients. The infraclavicular block was with a single injection posterior to the axillary artery, whereas the axillary block was with a triple stimulation technique.…”
Section: Comparison Between Brachial Plexus Block Approachesmentioning
confidence: 99%
“…Sensitivity US/NSt: 5 min: 3.36±2. 32 At the beginning of surgery complete nerve blockade was achieved in 89% in the US group and 68% in the NSt group (p=0.006), 3 (US) versus 7 (NSt) patients needed supplementation and 3 (US) versus 11 (NSt) patients needed general anesthesia (p=0.022). To achieve the nerve block took approximately 1 min more in the US group (p=0.003).…”
Section: Schlüsselwörtermentioning
confidence: 97%
“…Insbesondere bei der axillären und infraklavikulären Blockade orientieren sich viele Autoren bewusst nicht an den nervalen Strukturen, sondern an der A. axillaris als Leitstruktur [10, 12,22,27,32,33]. Dieses liegt u. a. daran, dass die nervalen Strukturen speziell in der infraklavikulären Region nicht immer eindeutig zu identifizieren sind.…”
Section: Diskussionunclassified